Pengembangan Desain Pembelajaran Matematika Berbantuan Aplikasi GeoEnzo untuk Menumbuhkan Kemampuan Metakognitif Siswa SMK Mega Link Majene - Syamsuddin Syamsuddin; Herlina Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
Covid-19 is affecting the world of education. Teachers are intended to change the paradigm of teaching methods, teachers face digital habits. The application of learning applications is an option in instilling mathematical concepts. The application of learning mathematics is one of the media that can be used by teachers in growing students' metacognitive abilities in understanding and solving mathematical problems. This type of research is a design research using the Plomp model with five stages, including: (1) initial assessment stage (2) design stage, (3) realization/construction stage, (4) test, evaluation and revision stage, and (5) stage implementation. This study aims to design three-dimensional learning assisted by the GeoEnzo application to foster students' metacognitive abilities in understanding and solving mathematical problems, especially three-dimensional material. The subjects of this study were students of class XII SMK Mega Link Majene which opened 40 people. This research resulted in: (1) the development of mathematical learning tools, especially on three-dimensional material that was valid, practical, and effective; (2) student activity observation sheets and teacher implementation; (3) student response questionnaires; and (4) learning outcomes test. The results of the research on the development of the GeoEnzo-assisted mathematics learning design are valid, practical, and effective for improving the metacognitive abilities of the students of SMK Mega Link Majene.